Porocarcinoma with perineural invasion - Ciara A Maguire (Indian Dermatology Online Journal, 2015)
Herein we present the case of a 58 year old woman with porocarcinoma of the left forehead with perineural invasion, diagnosed after recurrence of previously excised benign poroma. This case serves as a reminder of the potential of malignant degeneration within long-standing benign adnexal tumors as well as the spectrum of histological features that may be seen in porocarcinoma.